Zero-Padding techniques in OFDM systems - Al-Jawhar, Yasir Amer; Ramli, Khairun Nidzam; Taher, Montadar Abas; Mohd Shah, Nor Shahida; Audah, Lukman; Ahmed, Mustafa Sami (Science Publication Corporation (SPC), 2018)
Although the OFDM system has been gaining importance in recent years, the high peak to average power ratio is considered the main limitation of the system. The oversampling operation in the frequency-domain plays an essential role in the PAPR calculations precisely. The main purpose of the paper to draw attention to zero-padding methods which are used to oversampled baseband OFDM signals. Moreover, to study the influence of the zero-padding methods on the accuracy of the PAPR calculations, and the spectral spreading of the OFDM signals. Simulation results show that the zero-padding method which inserts the zeros at the center of the baseband OFDM signal is better than the other zero-padding methods in terms of both accuracy PAPR calculations and spectral distribution